Piezosurgery: Application in endoscopic otorhinolaryngology - M. Walsh; A. Quinn; L. Peeperkorn; B. Mahesh (Elsevier, 2022)
Introduction: The Piezosurgery® ultrasonic device (PZD) has been available for over three decades. Its application is limited in the realm of Otorhinolaryngology (ENT) particularly in conjunction with the endoscope. The safety profile allows the PZD, the ability to limit damage to soft tissue's such as nerves, dura and vessels offering reassurance in narrow confines. The reduced bleeding profile, enables better optics of the anatomical landscape. Case profile: Two cases performed with the endoscope portray this novel use of the PZD. The first case describes a patient, who previously underwent a Draf 3, with a residual bony frontal beak obstructing the outflow tract. The PZD facilitated debridement of the bone. The second case for a right attico-antrostomy, utilised the PZD with the endoscope, cholesteatoma was removed successfully. The patient had a previous iatrogenic dead ear on the contralateral side, thus hearing preservation was paramount. Discussion: There is a paucity of research on the application of the PZD in ENT, research primarily focuses on open surgery. There is concordance amongst papers on the manoeuvrability and visibility the PZD offers. From the early nineties the surgical microdebrider has been utilised in Functional Endoscopic Sinus Surgery, its rotating blade, does impose risk when dissecting close to the Orbit and Skull Base. Bleeding which obstructs the view through the Endoscope also increases the risk of complications. The PZD causes less tissue trauma and bleeding and potentially offers a safer alternative. Conclusion: Further prospective trials with larger numbers will no doubt augment the profile and application of the PZD in ENT.